Dendrocalamus jinghongensis (Poaceae, Bambusoideae), another new woody bamboo from Yunnan, China - Wang, Ping-Yuan; Zhang, Yu-Xiao; Li, De-Zhu; Liu, Wen-Jie (Phytotaxa, 2016)
Dendrocalamus jinghongensis, another new species of woody bamboos endemic to southern Yunnan, China, is described and illustrated. It can be distinguished from closely related species by the following morphological characters: branching from the nodes around 2 m above the ground; culm sheath 1/2 as long as the internode, culm sheath ligule 10–20 mm long; leaf sheath ligule 3–13 mm long; filaments free, or attached together only at the lower portion, and ca. 14 mm long.